2015
DOI: 10.1158/1055-9965.epi-14-0692
|View full text |Cite
|
Sign up to set email alerts
|

Clinic Type and Patient Characteristics Affecting Time to Resolution after an Abnormal Cancer-Screening Exam

Abstract: Background Research shows that multilevel factors influence healthcare delivery and patient outcomes. The study goal was to examine how clinic type (academic medical center (AMC) or federally-qualified health center (FQHC)) and patient characteristics influence time to resolution (TTR) among individuals with an abnormal cancer screening test enrolled in a patient navigation (PN) intervention. Methods Data were obtained from the Ohio Patient Navigation Research Project, a group-randomized trial of 862 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Further, TTR following an abnormal screening result followed patterns similar to national-level NBCCEDP data. (5, 12, 18, 23)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, TTR following an abnormal screening result followed patterns similar to national-level NBCCEDP data. (5, 12, 18, 23)…”
Section: Discussionmentioning
confidence: 99%
“…Other literature has found that TTR is associated with patient characteristics such as age, race-ethnicity, poverty level, insurance status, and BI-RAD category of abnormal screening result;(5, 12, 18) therefore, we also evaluated these variables as potential covariates, in addition to language preference and patient-reported health status (symptomatic/asymptomatic) at intake.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation